Simulation and experiment on prediction of total rice seeds mass in vibrating tray for vacuum plate seeder - Zhao, Zhan; Jin, Mingzhi; Tian, Chunjie; Qin, Fang (International Journal of Agricultural and Biological Engineering, 2019)
To improve the seeds pick-up precision of a vacuum plate seeder, it is important to accurately control the relative distance between suction plate and seeds layer in vibrating tray. Under the excitation of reciprocating vibration with a time varying interference in direction angle, the seeds motion is simulated using the discrete element method (DEM). By analyzing the seeds distribution characteristics, it was found that the seeds-mass-per-unit-area (SMA) was approximately plane distributed in the tray. Then, four square areas on the bottom of rectangular tray were divided symmetrically near the four vertices to measure the corresponding SMA respectively, and a monitoring plane model was established to predict the average SMA and total seeds mass in the tray. The prediction results of DEM simulation showed that the maximum and the mean relative errors were 6.75% and 2.85%. The influences of the normal vector of monitoring plane model and the standard deviation of SMA in four monitoring areas on the prediction errors were analyzed. A method for improving prediction accuracy by using linear regression correction was proposed, and the maximum and the mean relative errors could be reduced to 5.01% and 2.07%. When the tray was vibrated with the frequency of 11 Hz and the amplitude of 4 mm, experiments were carried out on the vacuum plate seeder test-rig. A Kalman filter was adopted to suppress the SMA measurement noise in four monitoring areas. Prediction results indicated that the maximum and the mean relative errors were 10.2% and 3.46% with the average SMA in range of 0.9-1.5 g/cm2, respectively. The paper can provide a basis for further study on the automatic control of suction plate motion according to the variation of seeds mass in the tray.Keywords: vacuum plate seeder, rice seeds, total mass, prediction method, vibrating tray, discrete element methodDOI: 10.25165/j.ijabe.20191205.4415Citation: Zhao Z, Jin M Z, Tian C J, Qin F. Simulation and experiment on prediction of total rice seeds mass in vibrating tray for vacuum plate seeder. Int J Agric & Biol Eng, 2019; 12(5): 81–86.